The Greek world of Apuleius : Apuleius and the second sophistic - Sandy, Gerald N. (Mnemosyne, Supplements, 1997)
The first three chapters of this book elucidate the scholastic goals of both classical cultures during the Roman Imperial period. Apuleius' works share the stage in these chapters with representatives of the second-century Greek cultural paradigm. They define patterns of discourse and fit selected examples of analogous Apuleian strategies into the broader cultural framework. Subsequent chapters focus closely on the complete Apuleian corpus under the general headings of Apuleius in the roles of orator, philosopher and novelist. Two of Apuleius' philosophical works and his novel the Golden Ass provide an unparalleled opportunity to analyze the methods of translation and adaptation employed by the major Latin writer of the second half of the second century.